Selection of Pin Component Sub Suppliers for Checking Fixture Products Using an Analytical Hierarchy Process Approach - Imansuri, Febriza; Aritama, Ditya; Sumasto, Fredy; Purwojatmiko, Handoko (Faculty of Industrial Technology Universitas Islam Indonesia, 2023)
The objective of this study is to employ a multi-criteria decision-making system technique to identify the most optimal supplier in the automotive components sector. When selecting a supplier, it is crucial to evaluate the pros and downsides of each source in order to secure the most suitable one. Bahana, Ltd is a company that specializes in the production of plastic components, molds, jigs, and equipment. During the production process of inspecting fixture items, pin components are required to assemble the components that need to be assembled. At now, there are no explicit guidelines for choosing suppliers, and the selection process relies solely on subjective evaluations. Consequently, it is necessary to establish supplier selection criteria through the utilization of the Analytical Hierarchy Process (AHP) methodology. This strategy is highly suitable for resolving decision-making challenges. Bahana, Ltd employs pairwise comparisons to evaluate four criteria: pricing, quality, communication, and location. Bahana, Ltd has the highest criteria value of 0.36 in terms of quality, followed by a value of 0.33 in terms of pricing. Hence, the paramount criteria in supplier selection are quality and pricing. According to the AHP calculation results, PT A was determined to be the optimal choice as it obtained the highest weight value in comparison to other suppliers.